Cecropin AD reduces viral load and inflammatory response against H9N2 avian influenza virus in chickens - Zhang, Taiming; Liu, Zhenyi; Zhi, Yan; Zhao, Xinping; Du, Mengze; Zhang, Qian; Zhang, Tao; Hu, Ge (Frontiers in Veterinary Science, 2024)
This investigation evaluates Cecropin AD, an antimicrobial peptide, for its therapeutic efficacy against H9N2 Avian Influenza Virus (AIV) in chickens. Using in vivo experiments on infected chickens, we assessed the impact of varying doses of Cecropin AD on lung pathology, viral titers, mast cell count and degranulation, and serum levels of inflammatory markers. A total of 108 5-week-old chickens were categorized into control, infected, and treatment groups, with the latter receiving Cecropin AD at high, medium, and low dosages. Post-infection, we analyzed the lung tissue and serum samples at multiple time points using Hemagglutination (HA) tests, histopathological and Toluidine Blue (TB) staining, real-time PCR, and enzyme-linked immunosorbent assays. The results indicated that Cecropin AD significantly mitigates pulmonary damage and viral load, particularly at higher dosages, paralleling the effects of conventional medication. Mast cell activity and inflammatory factors like IL-6, TNF-α, IFN-γ, and 5-HT were notably modulated by the peptide treatment, suggesting its potential to curb inflammation and viral proliferation. In conclusion, Cecropin AD emerges as a promising candidate for controlling H9N2 AIV in chickens, evidenced by its capacity to alleviate lung injury, reduce viral presence, and regulate immune responses.